2012
DOI: 10.1155/2013/539251
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Metal Levels in Paddy Soil, Rice Plants, and Rice Grains: A Case Study from Shakargarh, Pakistan

Abstract: The present study aims at determining the relationship between trace metal levels in paddy soils, rice plants, and rice grains obtained from these plants. The levels of selected metals (Fe, Co, Ni, Cd, Pb, and Cr) were determined by atomic absorption spectrophotometry in the soil, rice plants, and rice grain samples collected from paddy fields. All the metals were present at enhanced levels in paddy soil. Among the selected metals, Fe, Ni, Cd, and Cr were predominantly associated with oxidizable fraction. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 43 publications
5
13
1
Order By: Relevance
“…TF from shoot to rice grains was in the following order: japonica < indica < hybrid indica. However, TF of lead from root to shoot was non-significant also reported by Tariq and Rashid (2013) and Sharma and Dubey (2005). However, Burzynski and Grabowski (1984) concluded that decline in nitrate uptake might be due to moisture stress caused by Pb in the soil.…”
Section: Plant-nutrient Relationshipmentioning
confidence: 71%
“…TF from shoot to rice grains was in the following order: japonica < indica < hybrid indica. However, TF of lead from root to shoot was non-significant also reported by Tariq and Rashid (2013) and Sharma and Dubey (2005). However, Burzynski and Grabowski (1984) concluded that decline in nitrate uptake might be due to moisture stress caused by Pb in the soil.…”
Section: Plant-nutrient Relationshipmentioning
confidence: 71%
“…Cluster analysis has proved to be a milestone toward the source apportionment studies of various pollutants like metals and pesticides in the soil and other media [ 47 , 48 ]. In this analysis ( Figure 3 ), linkage distance is used as the measure of degree of closeness and hence relation among the various parameters [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Trace element accumulation in paddy systems is determined by several influences, such as the bioavailability of the metals, the physicochemical properties of the paddy soil, and the plant species of interest [272]. According to Tariq and Rashid (2012), the trace element concentrations in paddy soil are significantly correlated with plant uptake but insignificantly correlated with the physicochemical properties of paddy soils and the plant species. Therefore, through plant rhizosphere processes, trace element uptake is generally governed by the physicochemical properties of paddy soil.…”
Section: Trace Element Accumulation Influences In Paddy Soil-rice Systemsmentioning
confidence: 99%